2016
DOI: 10.1109/lra.2015.2508061
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Impedance Force-Tracking Control Design With Impact Formulation for Interaction Tasks

Abstract: The letter presents a force-tracking impedance controller granting a free-overshoots contact force (mandatory performance for many critical interaction tasks such as polishing) for partially unknown interacting environments (such as leather or hard-fragile materials). As in many applications, the robot has to gently approach the target environment (whose position is usually not well-known), then execute the interaction task. Therefore, the algorithm has been designed to deal with both the free space approachin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(66 citation statements)
references
References 21 publications
0
66
0
Order By: Relevance
“…After all creep experiments are completed, the data are averaged. e MATLAB fitting toolbox is used to fit the data by equation (2). e fitting results are shown in Figure 1.…”
Section: Viscoelastic Burgers Model Of Apple and Parametermentioning
confidence: 99%
See 1 more Smart Citation
“…After all creep experiments are completed, the data are averaged. e MATLAB fitting toolbox is used to fit the data by equation (2). e fitting results are shown in Figure 1.…”
Section: Viscoelastic Burgers Model Of Apple and Parametermentioning
confidence: 99%
“…In order to solve the problem of rapid compliant picking, many scholars have conducted a lot of research studies, and many studies have applied impedance control to it. For example, based on the optimal control theory, the set value of the internal impedance control layer was calculated by using the external admittance control layer, and the gain of the impact model was optimized to achieve the control performance with estimated error [2]. To realize the flexible adjustment of force and position of the manipulator under high-speed clamping and achieve good tracking effect, a robust impedance control method was proposed [3].…”
Section: Introductionmentioning
confidence: 99%
“…Indirect force control architectures address the problem of switching between controllers [14]. [15] proposed a two layers controller which consists of an impedance and an admittance controllers. The parameters of the latter are calculated by solving a Linear Quadratic Regulator problem to minimize the force overshooting.…”
Section: Introductionmentioning
confidence: 99%
“…if 0 < q δẋ, (25a) is monotonically decreasing and (25b) is monotonically increasing. Hence, based on (25b), q 1Tẋ (t * ) = δẋ at t * = −ln( ν ν+δẋ −q Tẋ δẋ, substituting (5),(15) and t * into (25a) yieldsq 1 T x(t * ) = (δẋ + ν)(−ω −1 ln( ν ν + δẋ − q 1 Tẋ )) + (q δẋ)ω −1 + q 1 T x 0 = (−(δẋ + ν) ln( ν ν + δẋ − q 1 Tẋ 0 ) − δẋ + q…”
mentioning
confidence: 99%
“…Similar to the contact force estimation, research in the field of impedance control extends beyond the field of spacecraft capture. One such example is the research perfomed by Roveda et al [36], who presented a forcetracking impedance controller which granted an overshoot-free contact force to allow interactions with partially-unknown environments using a modified linear quadratic regulator to analytically determine the optimal gains. A probing task was carried out and results have shown that the controller avoids force overshoots and instabilities.…”
Section: Compliant Spacecraft Capturementioning
confidence: 99%